Diagnóstico precoce do transtorno do espectro autista leve e sua relação com a crença de autoeficácia. - Cerqueira, Helena Ferreira (2024)
Since the Diagnostic and Statistical Manual of Mental Disorders V (DSM V) in 2013 many individuals previously diagnosed as Asperger's Disorder have now received a diagnosis of ASD without intellectual impairment. Since then, concerns have been raised that, as a result of the new guidelines, many children who previously have been diagnosed with Asperger's Disorder may no longer be considered to have the diagnosis or that they may be found even later. Self-efficacy beliefs regulate human functioning through cognitive, motivational, affective and decision-making processes. They consist of the judgment that a person makes about their ability to undertake a set of actions necessary to achieve their objectives. In this way, they influence individuals' thinking in a self-encouraging or self-weakening way and how well they motivate themselves and persevere in the face of difficulties. By seeking a correlation between perceived self-efficacy beliefs and early diagnosis of ASD, we intend to highlight the importance of screening and diagnosis in early childhood to contribute to the development and adaptation of individuals to society. In this sense, our hypothesis is that the diagnosis of ASD in childhood favors a higher self-efficacy belief in future life, since after the expected diagnosis, psychotherapeutic treatment tends to be provided in a practical way. This is a retrospective cross-sectional research. A sample, for convenience, was obtained through wide dissemination among private mental health professionals who have expertise with the target audience of the research. The inclusion criteria for participants were having a suspicion or diagnosis of mild ASD and having already been tested by a previously standardized IQ test, proving an IQ >70. 34 individuals (between 11 and 55 years old) of both sexes were selected. The socioeconomic level of the sample is that of a middle and upper class population. Two participants had to be excluded from the research because they did not score the ASD diagnosis on the ADOS scale. To carry out data collection, a sociodemographic questionnaire was applied. Confirmation of the diagnosis of ASD was made through the evaluation of the mental examination by a psychiatrist with expertise in ASD and application of the diagnostic instrument: Autism Diagnostic Observation Schedule, Second Edition (ADOS-2), by a professional (speech therapist), duly trained and accredited. In addition, the Perceived General Self-Efficacy Scale (EAGP) was applied. In total, there were 3 meetings: one with the psychiatrist to apply the sociodemographic and EAGP questionnaire and two with the speech therapist to apply the ADOS-2. The study's Cronbach's Alpha was measured, without meaning to evaluate the internal consistency of the instrument used. The correlation between the variables (perceived self-efficacy and age of diagnosis) was evaluated by calculating Spearman's Correlation Coefficient and Kendall's Correlation Coefficient, with the respective statistical tests of significance. Kendall's radiance coefficient indicated a positive and significant association. The same conclusions were obtained for the Spearman projection coefficient. As predicted, we concluded that there is a positive relationship between early diagnosis of ASD and better Perceived General Self-Efficacy in adult life.